TEORI PERKEMBANGAN IMAN REMAJA MENURUT JAMES W. FOWLER DAN IMPLIKASINYA BAGI PENDIDIKAN AGAMA KRISTEN - YUNARDI KRISTIAN ZEGA (Unika Santu Paulus Ruteng, 2020)
James W. Fowler is the originator of the Stages of Faith Theory. The level of faith development based on research conducted by Fowler is the structure, stages of faith development, and aspects that support so that every religious person does not stop at a low level of faith but can rise at a higher level and produce more mature humans . One of the targets of Fowler's research is adolescents. Teenagers are the age where children start trying to find their identity. Teen age is also a potential age in its development, both in terms of cognitive, emotional, and physical aspects. In addition, children at this age have a very high curiosity, one of which they begin to find out about the truth of the faith or beliefs that have been believed. Therefore, the perfect time to provide religious education at adolescence, so as to increase the development of adolescent faith to a higher stage so that they have an increasingly mature life and can also be responsible for the faith he has believed both for himself and for those who people around him. For that reason, in this article the author will discuss the stages of faith development, especially in adolescents according to the theory of James W. Fowler and their implications for Christian religious education in families, schools, and churches.